High-performance shape memory epoxy resin with high strength and toughness: Prepared by introducing hydrogen bonds through polycaprolactone and low melting point alloy - Tuo, Zhiwei; Chen, Kunzhi; Zhou, Qiang; Wang, Yubo; Wang, Qiushi; Zhang, Yuyu; Lin, Zhaohua; Liang, Yunhong (Composites science and technology, 2024)
Epoxy resin (EP) as common polymers have attracted much attention in the field of shape memory materials due to their excellent properties. However, epoxy-based shape memory polymers suffer from a trade-off between strength, toughness, variable stiffness capability and shape memory properties, and thus are subject to significant limitations in their applications. In this paper, we propose a method to prepare epoxy composites with high strength and toughness and high shape memory properties by introducing a lot of hydrogen bonds. Hydrogen bonding is generated through polycaprolactone (PCL) induced EP phase separation. A low melting point alloy (L) was also added to enhance the shape memory properties of the composites. The synthesis mechanism of EP and the formation mechanism of hydrogen bonding were revealed. The effects of the introduction of hydrogen bonding on the mechanical properties, stiffness and shape memory properties of the composites were investigated. New ideas and design directions are provided for the optimisation of modification of high-performance shape memory epoxy resins. [Display omitted] •Enhanced mechanical properties of resins achieved by induced phase separation.•Efficient dispersion of low melting point alloys in resins.•The mechanism of the effect of hydrogen bonding on resin properties is revealed.